2002
DOI: 10.1002/ijc.10339
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of stomach cancer in Mumbai, India

Abstract: Stomach cancer incidence rates are much lower in India than elsewhere, but the stomach remains one of the 10 leading sites of cancer in both sexes in most of the metropolitan registries. This is an unmatched case-control study of stomach cancer carried out at Tata Memorial Hospital (TMH), Mumbai. Our purpose was to identify the association of tobacco and alcohol use, occupational hazards, diet, consumption of beverages like tea and coffee, the living environment, cooking media and literacy with stomach cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 34 publications
3
47
2
Order By: Relevance
“…The habits of drinking alcohol and chewing "quid" (leaf of Piper betel containing small pieces of areca nut and a pinch of aqueous lime) did not emerge as risk factors in this study [7]. However, Rao et al [8] did not find any relation between tobacco use and risk of gastric cancer. In another study, a high consumption of rice with chilli, and the consumption of high-temperature foods were (sevenfold increased risk) found to be independent risk factors.…”
Section: Risk Factorscontrasting
confidence: 64%
“…The habits of drinking alcohol and chewing "quid" (leaf of Piper betel containing small pieces of areca nut and a pinch of aqueous lime) did not emerge as risk factors in this study [7]. However, Rao et al [8] did not find any relation between tobacco use and risk of gastric cancer. In another study, a high consumption of rice with chilli, and the consumption of high-temperature foods were (sevenfold increased risk) found to be independent risk factors.…”
Section: Risk Factorscontrasting
confidence: 64%
“…Probable high risk foods (salted fish, kipper, salted meat, kaleh pache (head and hoof soup)) was confirmed as a risk factor for gastric cancer incidence which is consistent with some studies (Rao et al, 2002;Kim et al, 2002;De Stefani et al, 2004;Strumylaitė et al, 2006). Although frequency, portion size and type of these foods were very important for interpreting of risk factors role, but many studies showed the potential side effects of permanent usage of this kind of foods.…”
Section: Discussionsupporting
confidence: 89%
“…15,16) These anti-tumor activities of green tea have been supported by epidemiological findings that green tea drinking lowers the risk of stomach cancer. 17,18) Other Japanese studies showed that consumption of green tea amounting to more than 10 cups per day lowered the incidence of cancers of the stomach, lung and other sites. [19][20][21] We previously reported that green tea polyphenols inhibit in vitro growth of ATL cells as well as HTLV-1-infected T-cells, by inducing apoptosis.…”
mentioning
confidence: 99%